Disruptive innovations and the challenges for banking. (13th September 2019) - Kjellman, Anders; Björkroth, Tom; Kangas, Taisto; Tainio, Risto; Westerholm, Thomas
In this article, we analyse the concepts of disruptive innovations, innovation platforms and potential ways forward for the banking industry in Europe. The choice of platform and place in the eco-system are strategic choices under a high degree of uncertainty. There is no quick fix, nor one size fits all banks, however, we find that banks need capable teams that are able to come up with viable solutions for the future, and the bank's platform.